2001
DOI: 10.1088/0953-2048/14/4/306
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of structure and transport properties of Gd1-x-zPrxCazBa2Cu3O7-δsystem

Abstract: The granular Gd 1−x−z Pr x Ca z Ba 2 Cu 3 O 7−δ (GdPrCa-123) high-temperature cuprate superconductor samples were prepared and characterized. The electrical resistivity of Pr-free samples show a reduction in T c with increasing Ca content. For these samples, the T c (z) curve is nonlinear and a plateau appears at z ≈ 0.05-0.15. With increasing Ca concentration, the lattice parameter a increases. Moreover, it is observed that the in-plane Cu(2)-O(2) bond distance increases with increasing Ca content. On the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
(43 reference statements)
3
13
0
Order By: Relevance
“…The lattice parameters and other fitted parameters are given in Table 1. It can be seen from the XRD patterns and fitted lattice parameters, that with increase in Ca concentration, the orthorhombicity of the structure decreases, which is in agreement with early studies [2,5,8]. Cava et al [1] measured the lattice parameters with different oxygen stoichiometry for pure YBCO.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The lattice parameters and other fitted parameters are given in Table 1. It can be seen from the XRD patterns and fitted lattice parameters, that with increase in Ca concentration, the orthorhombicity of the structure decreases, which is in agreement with early studies [2,5,8]. Cava et al [1] measured the lattice parameters with different oxygen stoichiometry for pure YBCO.…”
Section: Resultssupporting
confidence: 83%
“…For oxygen deficient or partially oxygenated structure, the T c increases with increasing Ca concentration by enhancing the overall hole density [2,6,9]. In contrast, in oxygen rich samples Ca substitution causes reduction of T c [2,5,[7][8][10][11]. This T c depression is unlikely to be due to over-doping alone.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…For fixed Pr and Ca concentrations (fixed x and y), T c is linearly dependent on rare earth ion size. However, Shakeripour et al 19 reported that their R 1−x−y Pr x Ca y Ba 2 Cu 3 O 7 samples contained impurity phase for x > 0.15 and y > 0.25. The aim of this research is to contribute to an understanding of this problem with substitution at RE site and Ba site.…”
Section: Introductionmentioning
confidence: 97%